2009
DOI: 10.1038/jid.2009.74
|View full text |Cite|
|
Sign up to set email alerts
|

Role for Protein Kinase C-α in Keratinocyte Growth Arrest

Abstract: Multiple protein kinase C (PKC) isoforms have been associated with the epidermal keratinocyte (KC) granular layer differentiation program. Here we show PKCalpha membrane localization and substrate phosphorylation in the first suprabasal KCs of normal human epidermis, suggesting activation in vivo in the lower spinous layers where terminal differentiation-associated growth arrest occurs. To determine if PKCalpha is sufficient for KC growth arrest, we expressed a constitutively active PKCalpha (PKCalpha Delta22-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 53 publications
3
41
0
Order By: Relevance
“…In our study, inhibition of lipin-1 expression by targeting which is accompanied by the induction of p21 in normal keratinocytes ( 49,50 ). Consistent with TPA treatment, overexpression of PKC ␦ and -␣ in keratinocytes prevents proliferation by a mechanism associated with elevated p21 expression ( 38,39 ). On the contrary, we found that lipin-1 KD-induced suppression and lipin-1-induced activation of PKC ␣ are associated with induction and inhibition of p21 expression, respectively, in NHEKs ( Fig.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…In our study, inhibition of lipin-1 expression by targeting which is accompanied by the induction of p21 in normal keratinocytes ( 49,50 ). Consistent with TPA treatment, overexpression of PKC ␦ and -␣ in keratinocytes prevents proliferation by a mechanism associated with elevated p21 expression ( 38,39 ). On the contrary, we found that lipin-1 KD-induced suppression and lipin-1-induced activation of PKC ␣ are associated with induction and inhibition of p21 expression, respectively, in NHEKs ( Fig.…”
Section: Discussionsupporting
confidence: 48%
“…In this study, we show that PKC ␣ activation is regulated by lipin-1 in NHEKs. PKC ␣ is expressed and activated in the fi rst basal or lower spinous layers in human epidermis ( 39 ). These results suggest that lipin-1 may be involved in PKC ␣ activation in the basal and spinous layers the fi nal reaction in TAG synthesis die shortly after birth due to abnormal energy metabolism and impaired skin permeability barrier function ( 46 ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The low proliferative ability and enhanced differentiation of keratinocytes cultured in pantothenic acid-deficient DMEM indicate that the depletion of pantothenic acid may decelerate or arrest the cell cycle, thus enhancing keratinocyte differentiation (9). It is known that the balance between proliferation and differentiation is regulated by various factors, and protein kinase C or tyrosine kinase may be involved in the "switch" from proliferation to differentiation (10), although the detailed mechanism has not been reported. Moreover, it has been shown that an increased intracellular Ca 2+ concentration or high cell density might induce cell differentiation (11).…”
mentioning
confidence: 99%